Evaluasi Kesesuaian Model Keperilakuan dalam Penggunaan Teknologi Sistem Informasi di Indonesia - Ardi Hamzah (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2009)
The change of behavior in an organization becaused organization structure, new information systemtechnology usage and environment outside organization. The usage of new information system technology orreplacement usage of new information system technology will also change individual behavior in organization.The change of individual behavior on information system techhnology related with individual performancebecaused some factors, i.e. individual attitude, subyektif norms, intention, behavior control, acceptance toinformation system technology, technology – performance chain, trust to technology, psikological attachmentand qualitatif characteristic of information system technology. The existence some factors appear some modelsof behavior in usage of information system technology. This matter, neccessary evaluation on some models ofbehavior which appropriate with intention individual and need organization until the impact at satisfaction andimprovment performance of individual and organization.Keywords: Behavior, Information System Technology, Models of Behavior